Children with Severe Acute Malnutrition, Aged 5 to 60 Months, Admitted to Department of Pediatrics MMC Mardan, Pakistan Clinical Profile and Outcomes - Muhammad Qasim Khan, Kiramatullah, Inayat Ullah, Haji Gul Afridi, Sijad-Ur-Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The current study's goals were to ascertain the prevalence of , the clinical profile associated with , including risk factors, co-occurring diseases, and the kind of , as well as to ascertain how would fare following hospitalization and treatment. Study Design: Single Center study Place and Duration of Study: This study was conducted at the department of Pediatrics, department of pediatrics mmc mardan Pakistan from Jan 2020 to Jan 2021. Materials and Methods: Following compliance with the inclusion criteria, 100 infants between the ages of 5 and 62 months were enrolled in the research. Data from the past, the clinic, and the lab were entered into a pre-made proforma. Using the suitable statistical methodology, data were evaluated. Results: Severe acute malnutrition is present in 02.09% of the population.The study population's average age is 20.76 13.80 months.Out of the 100 kids, 69% were male and 31% were female. There were more non-edematous (57%) than edematous (43%).The age range from 0 to 26 months had the highest incidence (67%).95% of the cases (almost all) were from low SES.Mothers just attended basic school or had no education (76%). EBF was only present in 17% of instances up to the age of six months. The most common clinical symptoms were vomiting (35%), diarrhea (69%), fever (67%), anorexia (65%), ARI (57%), and eye difficulties (34%).Anemia (87%), pneumonia (41%), worm infestation (39%) were the most common comorbid illnesses, followed by UTI (33%) and TB (16%). 54% of recoveries are made. The typical hospital stay lasts 10.28 days. 2 kids (4%) died while they were hospitalized. Conclusion: The most serious kind of malnutrition, severe acute malnutrition is a medical emergency that needs immediate intervention. It is probable to disrupt the vicious cycle of undernourishment and infection with prompt diagnosis and management of many risk factors, clinical and comorbid conditions, and hence improve result. Keywords: female literacy, Severe acute malnutrition, socio-economic status, wasting